The Legal Issues of Firearms Trafficking in the United States of America - A. V. Ravnyushkin (Сибирское юридическое обозрение, 2023)
Relevance and subject of research. The circulation of firearms as a source of increased danger is subject to legal regulation and control in the Russian Federation. The use of weapons by police officers is no exception. The norms of the Federal Law of February 7, 2011 No. 3-FZ “About the Police” (hereinafter referred to as the Law “About the Police”) refer to the achievements of domestic administrative science as a result of the work of specialists. In systemic connection with the norms of criminal law, they regulate the conditions and limits for the use of coercive measures by police officers, including firearms. The fundamental ideas of the activities of the Russian police have successfully cooperated with the norms of international law. On the contrary, in the socalled “leading” democratic state – the United States of America, such cooperation does not look well-coordinated, which the Author substantiates when studying the origins of the right of citizens of this state to own firearms, the regulatory regulation of the circulation of weapons in the United States, the negative consequences of this regulation (based on research by American scientists and statistical data), the activities of the US police to counter armed attacks and its legal regulation. One of the US attempts to comply with international law in this area is analyzed, namely the adopted new policy of the US Customs and Border Protection on the use of force, including firearms.The purpose of the study is to determine the state of legal regulation of the circulation of civilian firearms in the United States, the use of these weapons as a coercive measure by police officers in order to identify its positive aspects, in the presence of which the decision on the possibility / impossibility of their introduction into Russian legislation. This led to the setting of the following tasks: to study the constitutional foundations of the right to own firearms by US citizens (historical aspect); to determine the current state of legal regulation of civilian circulation of firearms in the United States and its consequences; analyze the activities of the US police to counter armed attacks and its legal regulation, evaluate them and determine the prospects for their improvement; identify the provisions of American legislation that are of scientific interest, and the possibility / impossibility of their implementation in Russian legislation.The methodological basis of the study was a dialectical approach to the scientific knowledge of social relations associated with the circulation of firearms, the implementation of their state regulation, analysis and synthesis of the results obtained during the study, which made it possible to formulate and substantiate the conclusions. Among the special methods used in the study are the method of studying normative legal acts and documents, the empirical method, the method of processing and analyzing data, and their generalization. Findings. The study shows that the constitutional foundations for the right to own firearms by US citizens developed simultaneously with the emergence of statehood: first in individual states, and then in the very union of these states formed into a single US government. The existing multi-layered legal framework for regulating the circulation of firearms has created a wide range of owners with a relatively simple system of access, which negatively affects the criminal environment, in which armed attacks with mass casualties are of high importance. Cases of armed attacks and other negative illegal acts to a certain extent influenced the processes of militarization of the police, the creation and strengthening of special operations units, the adoption by the police of various types of military equipment, weapons and special means. Detailed legal regulation of the use of lethal force by the police is developing belatedly. The 2014 adoption of the U.S. Customs and Border Protection Manual did not prompt other law enforcement agencies to adopt similar rules, indicating the fragmentation of U.S. law enforcement. The U.S. Customs and Border Protection Guidelines on the use of force is of particular scientific interest, and after its careful analysis, it is possible to introduce certain provisions into the legal regulation of the activities of the Russian police, especially the use of lethal force. The fundamental ideas of police activity developed in Russia can be recognized as certain guidelines for the development of the American police. The relatively small number of firearm owners in Russia and the high requirements for the circulation of firearms are a deterrent to the negative developments taking place in the United States.